2019
DOI: 10.1111/jssr.12616
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Decline of Evangelicals, Fundamentalists, Pentecostals, and Charismatics in Switzerland 1970–2013

Abstract: This article describes and explains patterns of growth and decline undergone by evangelical, fundamentalist, and Pentecostal/Charismatic (EFPC) denominations in Switzerland from 1970 to 2013. We combine data from different censuses, membership registers of denominations, and a National Congregation Study (NCS) to establish and explain patterns of growth and decline. Our main results are that (1) the overall EFPC milieu has grown since the 1970s; (2) the growth is predominantly caused by a rather strong increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Low levels of cohesion are observed even within the church communities, particularly among the stricter Pentecostal missionaries. Notably, Stolz and Favre (2019) report significant growth of evangelical, fundamentalist, and Pentecostal/Charismatic denominations in Switzerland from 1970 to 2013, but such growth is not associated with the strictness of the denomination.…”
Section: Literature On Screening and Commitment: Theory And Findingsmentioning
confidence: 99%
“…Low levels of cohesion are observed even within the church communities, particularly among the stricter Pentecostal missionaries. Notably, Stolz and Favre (2019) report significant growth of evangelical, fundamentalist, and Pentecostal/Charismatic denominations in Switzerland from 1970 to 2013, but such growth is not associated with the strictness of the denomination.…”
Section: Literature On Screening and Commitment: Theory And Findingsmentioning
confidence: 99%
“…Although scholars have increasingly challenged the popular assumption that P/Cs and Evangelicals experience a tension between this-worldly and otherworldly concerns (Heist and Cnaan 2016; King 2012, 924), studies have nevertheless shown them to be at least more likely to prioritize evangelism (Chaves 2017, 92; Smith 1998, 36–3; Wuthnow 2009, 141). These differences notwithstanding, some have shown that P/Cs are particularly proficient at “recruitment” (Stolz and Favre 2019, 621) and adept in their uses of mass media (Meyer 2010, 123). Given that much of the Christian Gospel is relayed not only through face-to-face proselytization but also television and radio programming or published Christian literature, P/C agencies that realize their comparative advantage will be more likely than Evangelical agencies to focus on otherworldly activities that facilitate this proliferation and propagation of the Gospel.…”
Section: The Pentecostal/charismatic-evangelical Dividementioning
confidence: 99%
“…With respect to P/C and Evangelical differences, studies on the global expansion of the former have cited a deprivation thesis, which argues that P/Cs are particularly effective in winning converts because they have a unique appeal to those experiencing “deprivations” such as poverty. The P/C subculture thus offers resources to cope, including “a symbolic toolbox that helps them interpret and manage the situations of deprivation”, “promises of immediate and future gains concerning health, wealth, and happiness”, “a sense of religious and social worth and identity,” and practical benefits such as “comfort, normative guidance, structuring of time, and interpersonal help” (Stolz and Favre 2019, 606).…”
Section: The Pentecostal/charismatic-evangelical Dividementioning
confidence: 99%
See 1 more Smart Citation
“…While converts to liturgical worship produce numerous arguments in its favour (Galli 2008;Webber 2008;Hunter 2011;Smith 2013;Holtzen and Hill 2016;Wilson 2019;Oxenreider 2020;Bevins 2020), converts to non-liturgical worship are less vocal about their reasons. They tend to be better observed statistically by the explosive growth of Charismatic, Pentecostal, and Evangelical Christianity around the world, of which the vast majority is non-liturgical (Stoll 1990;Anderson 2013;Martin 1994;Stolz and Favre 2019;Moberg and Skjoldli 2018;Hoon 2013).…”
Section: Introductionmentioning
confidence: 99%